Insights into a remote cryosphere: a multi-method approach to assess permafrost occurrence at the Qugaqie basin, western Nyainqêntanglha Range, Tibetan Plateau - Buckel, Johannes; Reinosch, Eike; Hördt, Andreas; Zhang, Fan; Riedel, Björn; Gerke, Markus; Schwalb, Antje; Mäusbacher, Roland (The Cryosphere, 2021)
Permafrost as a climate-sensitive parameter and its occurrence and distribution play an important role in the observation of global warming. However, field-based permafrost distribution data and information on the subsurface ice content in the large area of the southern mountainous Tibetan Plateau (TP) are very sparse. Existing models based on boreholes and remote sensing approaches suggest permafrost probabilities for most of the Tibetan mountain ranges. Field data to validate permafrost models are generally lacking because access to the mountain regions in extreme altitudes is limited. The study provides geomorphological and geophysical field data from a north-orientated high-altitude catchment in the western Nyainqêntanglha Range. A multi-method approach combines (A) geomorphological mapping, (B) electrical resistivity tomography (ERT) to identify subsurface ice occurrence and (C) interferometric synthetic aperture radar (InSAR) analysis to derive multi-annual creeping rates. The combination of the resulting data allows an assessment of the lower occurrence of permafrost in a range of 5350 and 5500 m above sea level (a.s.l.) in the Qugaqie basin. Periglacial landforms such as rock glaciers and protalus ramparts are located in the periglacial zone from 5300–5600 m a.s.l. The altitudinal periglacial landform distribution is supported by ERT data detecting ice-rich permafrost in a rock glacier at 5500 m a.s.l. and ice lenses around the rock glacier (5450 m a.s.l.). The highest multiannual creeping rates up to 150 mm yr−1 are typically observed on these rock glaciers. This study closes the gap of unknown state of periglacial features and potential permafrost occurrence in a high-elevated basin in the western Nyainqêntanglha Range (Tibetan Plateau).